IMPROVING THE WRITING SKILLS ON INVITATION CARD USING WRITING PICTURE LEARNING MODEL IN CLASS X STUDENTS OF SMK KARYA NATIONAL KUNINGAN - Ricky Yogie Pramukti (Indonesian Journal of Education Teaching and Learning (IJETL), 2023)
This aims of this research to determine the improvement of invitation card writing skills by applying the writing picture learning model. This research is Classroom Action Research (PTK) using the Kemis and Mc Taggart model. The research was carried out at Karya Nasional Kuningan Vocational School for class X students. The research data was analyzed using quantitative descriptive statistics. The results show that the writing picture learning model can increase student learning activities, namely in cycle I. Students achieved an average score of 7.0 with details: a score of 8.5 in the good category for 4 students (13%), a score of 8 in the good category for 8 students (25%), a score of 7 2 students (6%) in the sufficient category, 18 students (56%) in the almost sufficient category. So that in cycle I it can be categorized into almost sufficient groups. The average score achieved by students in this second cycle was 80 with details of a score of 90 with a very good category of 5 students (16%), a score of 85 in the good category of 8 students (25%), a score of 80 in the good category of 4 students (13 %), a score of 75 categories is more than sufficient for 12 students (38%) and a score of 7 categories is sufficient for 3 students (9%), so it can be concluded that the students' skills in writing invitation cards using the writing picture learning model in cycle II are in the group Good. Based on the research findings above, it can be concluded that applying the writing picture learning model can improve invitation card writing skills in English lessons.